Wiskott–Aldrich syndrome that was initially diagnosed as immune thrombocytopenic purpura secondary to a cytomegalovirus infection. (6th January 2018) - Kaneko, Ryota; Yamamoto, Shohei; Okamoto, Naoko; Akiyama, Kosuke; Matsuno, Ryosuke; Toyama, Daisuke; Hoshino, Akihiro; Imai, Kohsuke; Isoyama, Keiichi
Wiskott–Aldrich syndrome is a rare X-linked recessive disease resulting from variations in the WAS gene. Wiskott–Aldrich syndrome is sometimes difficult to differentiate from immune thrombocytopenic purpura. A 2-month-old boy was admitted to our hospital for purpura and thrombocytopenia. His mean platelet volume was reported to be normal. Treatment with intravenous immunoglobulins failed to improve the patient's platelet count. Subsequently, an acute cytomegalovirus infection was confirmed by serological testing and antigenemia. The patient was diagnosed with immune thrombocytopenic purpura secondary to a cytomegalovirus infection. However, based on the patient's clinical course and the refractoriness of his condition, Wiskott–Aldrich syndrome was strongly suspected. Through direct sequencing of the genomic DNA of the Wiskott–Aldrich syndrome protein (WASP) gene, we identified a novel missense mutation in exon 3 of the patient's WASP gene (c. 343 C>T, p. H115T), and the patient was diagnosed with Wiskott–Aldrich syndrome at 3 months after onset. Children with Wiskott–Aldrich syndrome are often initially diagnosed with immune thrombocytopenic purpura, which can lead to inappropriate treatment and delays to life-saving definitive therapy. Our findings imply that Wiskott–Aldrich syndrome should be considered as a differential diagnosis in cases of refractory immune thrombocytopenic purpura combined with a cytomegalovirus infection.